Arbuscular mycorrhizal fungi enhance the growth of the exotic species Ambrosia artemisiifolia. (2nd August 2021) - Kong, Lingjie; Chen, Xue; Yerger, Ellen Heininger; Li, Qiao; Chen, Fengxin; Xu, Haiyun; Zhang, Fengjuan
Abstract: Arbuscular mycorrhizal fungi (AMF) can increase host plant nutrient uptake via their mycelium, thus promoting plant growth. AMF have always been associated with successful invasion of most exotic plant species. However, knowledge regarding how AMF affect the success of plant invasion remains limited. Exotic Ambrosia artemisiifolia is an invasive and mycorrhizal plant species. A long-term field experiment was conducted to examine the differences in AMF diversity and composition in the roots of A. artemisiifolia and Setaria viridis subjected to interspecific competition during growth. A greenhouse experiment was also performed to test the effect of Funneliformis mosseae on the growth of these two species. Ambrosia artemisiifolia invasion caused AMF diversity to change in native S. viridis roots. Meanwhile, the relative abundance of F. mosseae was significantly higher in the roots of A. artemisiifolia than in those of S. viridis . The higher AMF colonization rate in the exotic species ( A. artemisiifolia ) than in the native species ( S. viridis ) was found in both the field and greenhouse experiments. The greenhouse experiment possibly provided that AMF advantaged to the growth of A. artemisiifolia, by influencing its photosynthetic capacity as well as its phosphorus and potassium absorption. These observations highlight the important relationship of AMF with the successful invasion of A. artemisiifolia .